Making geography matter: The past and present of a changing discipline - Castree, Noel; Barnes, Trevor; Salmond, Jennifer
What is the purpose of Geography? What do geographers study and why? How do they seek to shape the world they interrogate? This book addresses these questions by examining the lives and works of individual geographers, both past and present. Like all disciplines, Geography is no more nor less than the collective endeavours of researchers and teachers operating in specific contexts. The contexts both shape, and are shaped by, these individuals. This book's biographical and autobiographical chapters transport readers to the times and places where geographers have sought to make Geography matter.